2005
DOI: 10.1126/stke.2712005tr5
|View full text |Cite
|
Sign up to set email alerts
|

Ras-MAPK Pathways

Abstract: This Teaching Resource provides lecture notes and slides for a class covering three kinase-mediated signaling pathways and is part of the course "Cell Signaling Systems: A Course for Graduate Students." The focus is three major signaling cascades that are implicated in cell proliferation, survival, and stress response. They are, respectively, the mitogen-activated protein kinase (MAPK), phosphatidylinositol 3-kinase (PI3K), and Jun N-terminal kinase (JNK) cascades. The aim of this lecture is to review the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As one of the most distinctive members of mitogen‐activated protein kinase family, the pathway for ERK is synonymous with cell proliferation. The expression of YKL‐40 is related to expression of phosphorus ERK1/2, which is strongly associated with poor response to radiotherapy and negative results . In addition, Zhang et al showed that the expression of phosphorus ERK1/2 significantly decreases in U87 cells when YKL‐40 extinguishes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of the most distinctive members of mitogen‐activated protein kinase family, the pathway for ERK is synonymous with cell proliferation. The expression of YKL‐40 is related to expression of phosphorus ERK1/2, which is strongly associated with poor response to radiotherapy and negative results . In addition, Zhang et al showed that the expression of phosphorus ERK1/2 significantly decreases in U87 cells when YKL‐40 extinguishes.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of YKL-40 is related to expression of phosphorus ERK1/2, which is strongly associated with poor response to radiotherapy and negative results. 8,34 In addition, Zhang et al 8 showed that the expression of phosphorus ERK1/2 significantly decreases in U87 cells when YKL-40 extinguishes. Considering the important role of the PI3K signaling pathway in expression of YKL-40 and its expression by resveratrol through the PI3K signaling pathway and, on the other hand, considering that probably prednisolone can It's effects of apoptotic, anti-inflammatory, and inhibition of growth and proliferation of cancer cells through the same signaling pathway is done.…”
Section: Resveratrol and Prednisolone Downregulate Ykl-40 Protein In ...mentioning
confidence: 99%
See 1 more Smart Citation